THE DIFFERENCE OF STUDENT’S SPATIAL ABILITY TAUGHT BY USING COOPERATIVE LEARNING TPS WITH STAD FOR GRADE VIII IN SMP NEGERI 4 PAKKAT - Sarah . Uly; Edi . Syahputra (Universitas Negeri Medan, 2020)
ABSTRACTThe aim of this research is to know whether student's Spatial Ability taught by using Cooperative Learning TPS type is higher than Cooperative Learning STAD Type for Grade VIII in SMP Negeri 4 Pakkat. The population is all students of grade VIII in SMP Negeri 4 Pakkat. Sampling Techniques that is used in this research is random sampling. There are two samples in this research namely, Experimental class A is VIII-A taught by cooperative learning TPS and Experimental class B is VIII-B taught by cooperative learning STAD. Each of class consist of 34 students. This research using pretest and posttest where, data of pre test and post test are normal distribution and homogeneous. The result of the research shows that the average score of pretest in experiment class A and B are 37,6176 and 43,9142. After doing treatment in experiment class A and B obtained average score of posttest are 84,911 and 80. Hypothesis testing that have been conducted in this research is by calculating manually and results of hypothesis test of data from both experimental class in post test was found that. It indicates that H₀ is rejected. So, we can conclude that Students’ spatial ability taught by using cooperative learning TPS type is higher than cooperative learning STAD type.Keyword: Spatial Ability, TPS, STAD ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui apakah Kemampuan Spasial Siswa yang diajarkan dengan menggunakan model pembelajaran TPS lebih baik daripada model pembelajaran STAD untuk Kelas VIII di SMP Negeri 4 Pakkat. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah random sampling. Ada dua sampel dalam penelitian ini yaitu, Kelas A adalah VII-A yang diajarkan oleh TPS dan Kelas B adalah VII-B yang diajarkan oleh STAD. Masing-masing kelas terdiri dari 34 siswa. Teknik analisis data terdiri dari normalitas, homogenitas, dan uji hipotesis. Penelitian ini menggunakan pretest dan posttest dimana hasil pretest dan postest berdistribusi normal dan homogen. Hasil penelitian ini menunjukkan rata-rata nilai pretest di kelas A dan kelas B adalah 37,6176 dan 43,9142. Setelah melakukan pembelajaran di kelas A dan B rata-rata nilai posttest nya menjadi 84,911 dan 80. Uji Hipotesis pada penelitian ini dihitung secara manual dan hasil uji hipotesis dari kedua kelas tersebut didapat bahwa ini mengakibatkan H0 ditolak. Sehingga dapat disimpulkan bahwa model pembelajaran TPS lebih tinggi daripada model pembelajaran STAD.Kata kunci: Kemampuan Spasial, TPS, STAD